2003
DOI: 10.1046/j.1365-2125.2003.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro interethnic comparison of monoamine oxidase activities between Japanese and Caucasian livers using rizatriptan, a serotonin receptor 1B/1D agonist, as a model drug

Abstract: An in vitro interethnic comparison of monoamine oxidase activities between Japanese and Caucasian livers using rizatriptan, a serotonin receptor 1B/1D agonist, as a model drug Development, Banyu Pharmaceutical Co., Ltd, Kamimutsuna, Okazaki, and 3 Clinical Development Institute, Banyu Pharmaceutical Co., Ltd, Nihonbashi, Japan Aims Monoamine oxidase (MAO) is located in human liver, and catalyses the oxidative deamination step of many xenobiotics. However, whether there exists an interethnic difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…As above mentioned, CYP1A2 metabolism is less susceptible to ethnic differences. As for MAO activity, limited data are available on any ethnic differences in intestinal and hepatic MAO distribution, although Iwasa et al demonstrated that the hepatic MAO‐A and B activities in Japanese do not differ from or are fairly close to those in Caucasians. Therefore, low oral bioavailability potential contribution to ethnic difference in rasagiline PK is limited.…”
Section: Discussionmentioning
confidence: 99%
“…As above mentioned, CYP1A2 metabolism is less susceptible to ethnic differences. As for MAO activity, limited data are available on any ethnic differences in intestinal and hepatic MAO distribution, although Iwasa et al demonstrated that the hepatic MAO‐A and B activities in Japanese do not differ from or are fairly close to those in Caucasians. Therefore, low oral bioavailability potential contribution to ethnic difference in rasagiline PK is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Almotriptan and zolmitriptan are metabolized by MAO and multiple CYPs, with the involvement of CYP1A2 [523,524]. Rizatriptan is mainly metabolized by MAO-A via oxidative deamination [525]. Propranolol, but not metoprolol and nadolol, increased its AUC by 70% through MAO-A inhibition [526].…”
Section: Anti-migraine Drugsmentioning
confidence: 98%
“…Gómez et al (1988) demonstrated the presence of MAO-A and MAO-B activity in rat liver microsomes using enzyme-specific substrates and inhibitors and changes in temperature and pH sensitivity that were similar to those in mitochondria. Iwasa et al (2003) found that MAO activity for the metabolism of rizatriptan was similar between the microsomal and mitochondrial fractions of Japanese liver donors. In the present study, microsomal MAO activity seems to be qualitatively similar to that in the mitochondrial preparation.…”
Section: O Glucmentioning
confidence: 91%